Prestasi Belajar Siswa Ditinjau Dari Kecanduan Game Online dan Motivasi Belajar - Briti Nursita; Yansen Alberth Reba; Sirjon Sirjon (Psychocentrum Review, 2021)
The low student achievement is indicated because it is influenced by the level of game online and students learning motivation. The purposes of this study are 1) to determine the effect of online game addiction and learning motivation on learning achievement. 2) what is the percentage of the effect of online game addiction and learning motivation on learning achievement. Amounted 132 students with a sample 100 students who were determined by taking Non-Probability Sampling with the Accidental Sampling technique. To collect the data used questionnaire. Data analysis using regression test. The results of this study indicate that online game addiction and learning motivation contribute to student achievement by 65.1%. This means that 65.1% of the factors that effect student achievement are game addiction and learning motivation. The results obtained in this study can be used as input for BK teachers in an effort to reduce online game addiction and learning motivation with student achievement.